2011
DOI: 10.1124/jpet.111.180521
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hypoxia-Inducible Factor-1α in Acetaminophen Hepatotoxicity

Abstract: Hypoxia-inducible factor-1␣ (HIF-1␣) is a critical transcription factor that controls oxygen homeostasis in response to hypoxia, inflammation, and oxidative stress. HIF has been implicated in the pathogenesis of liver injury in which these events play a role, including acetaminophen (APAP) overdose, which is the leading cause of acute liver failure in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 40 publications
(62 reference statements)
1
26
0
Order By: Relevance
“…Furthermore, reoxygenation following hypoxic ischemia may also contribute to mitochondrial dysfunction and liver injury, as described (Moon, Hood, et al, 2008). Hypoxia-related liver injury due to CYP2E1-dependent metabolism of its potentially toxic substrates such as APAP, halothane, and CCL4 can be also observed in acute DILI, as reported ( James, Donahower, Burke, McCullough, & Hinson, 2006;Noll & De Groot, 1984;Sparkenbaugh et al, 2011). However, Lieber (2005) suggested that APAP-induced liver injury could be worse during alcohol withdrawal, due to less competition by alcohol for the CYP2E1-dependent metabolism of APAP.…”
Section: Role and Regulation Of Cyp2e1 In Liver Diseasementioning
confidence: 81%
“…Furthermore, reoxygenation following hypoxic ischemia may also contribute to mitochondrial dysfunction and liver injury, as described (Moon, Hood, et al, 2008). Hypoxia-related liver injury due to CYP2E1-dependent metabolism of its potentially toxic substrates such as APAP, halothane, and CCL4 can be also observed in acute DILI, as reported ( James, Donahower, Burke, McCullough, & Hinson, 2006;Noll & De Groot, 1984;Sparkenbaugh et al, 2011). However, Lieber (2005) suggested that APAP-induced liver injury could be worse during alcohol withdrawal, due to less competition by alcohol for the CYP2E1-dependent metabolism of APAP.…”
Section: Role and Regulation Of Cyp2e1 In Liver Diseasementioning
confidence: 81%
“…It is likely that the cellular mechanisms used by acetaminophen to produce toxicity may, in a lower dose range, mediate its therapeutic effects. In this regard, toxicity resulting from high dose acetaminophen is in part mediated by thrombin (Ganey et al, 2007; Sparkenbaugh et al, 2011). Thus, we explored whether thrombin is a mediator of acetaminophen’s beneficial effects on brain endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Acetaminophen hepatotoxicity has also been associated with HIF-1α activation, secondary to ROS formation (Chaudhuri et al 2011). Interestingly, HIF-1α-deficient mice exhibit attenuated acetaminophen hepatotoxicity at 6 h, but developed severe liver injury by 24 h, suggesting that HIF-1α is involved in the early stage of APAP toxicity, but protective at later time points (Sparkenbaugh et al 2011). Several other hepatotoxins, including amiodarone, diclofenac, troglitazone, and cyclosporine A, increase glycolysis and subsequent lactate production in cultured liver cells, (Limonciel et al 2011), a process that may be linked to HIF-1α activation.…”
Section: Hif-1α Pathwaymentioning
confidence: 96%